EXTENDING THE TECHNOLOGY ACCEPTANCE MODEL (TAM) TO ASSESS STUDENTS’ BEHAVIORAL INTENTIONS IN USING MOODLE AS AN LMS IN ENGLISH CLASS AT SMK NEGERI 3 MAGELANG - Khairunnisa Wijayanti; Daniel Ari Widhiatama; Muhammad Irfan Rumasoreng (Jurnal Scientia, 2023)
The blended learning model is a learning model that is popularly used, especially after the end of the Covid-19 pandemic, because blended learning combines face-to-face learning that interacts directly between teachers and students with online learning that utilizes the development of technology. In utilizing the blended learning model, Moodle is used as one of the LMS. In implementing the use of technology such as Moodle, there must be an adaptation of its use. Different factors influence and determine technological acceptability and adaptability. The objective of this study was to investigate the students’ behavioral intentions in using Moodle as an LMS in English class at SMK Negeri 3 Magelang and to know the students’ suggestions to improve the performance of Moodle as an LMS in English class at SMK Negeri 3 Magelang. As the research's theory base, an extended version of the technology acceptance model (TAM) was used. This study used a quantitative design where data were obtained from questionnaires, interviews, and observations with 142 students in the English class at SMK Negeri 3 Magelang. The data was analyzed using the Structure Equation Modeling (SEM) technique. The research findings revealed that the factors perceived credibility, satisfaction, attitude, and perceived usefulness positively influenced the students’ behavioral intentions in using Moodle as an LMS in English class at SMK Negeri 3 Magelang. Students also provide suggestions for improving the performance of Moodle by improving the quality of Moodle itself, improving the quality of each feature, fixing existing constraints, and adding various other interesting features.